Inefficiencies in Computed Tomography Sinus Imaging for Management of Sinonasal Disease: Results of a Tertiary Care Center. (10th January 2017) - Sharma, Giriraj K.; Foulad, Allen; Shamouelian, David; Bhandarkar, Naveen D.
Abstract : Objective: A subset of patients with sinonasal disease who obtain a diagnostic computed tomography (CT) sinus scan may require repeat preoperative CT due to the inadequacy of diagnostic CT for image‐guided sinus surgery (IGSS). This leads to increased CT utilization, health care costs, and patient exposure to ionizing radiation. The objective of this study is to determine the frequencies of diagnostic CT sinus studies that were inadequate for IGSS and repeat CT studies for purposes of IGSS. Study Design: A retrospective chart study was performed between May 2012 and August 2013. Setting: Tertiary care rhinology practice. Subjects and Methods: New patients with any sinonasal diagnosis who presented with CT sinus scans acquired from outside institutions were included. CT scans were considered inadequate for IGSS for any of the following reasons: >1.5‐mm slice thickness, oblique axial planes due to gantry tilt, and incompletely defined or missing IGSS anatomic landmarks. Results: Of 183 patients, 85 (46%) presented with diagnostic CT sinus scans that were inadequate for IGSS. Seventy‐one patients met indications for IGSS, of which 37 (52%) required repeat CT due to an IGSS‐inadequate diagnostic scan. Conclusion: The frequency of repeat preoperative CT sinus imaging may be high at tertiary care centers where IGSS is performed. A standardized IGSS‐adequate CT sinus protocol may avoid the need for repeat preoperative scans. Potential advantages include improved efficiency, decreased health care costs, and reduced ionizing radiation exposure to the patient.